Permanent Junctional Reciprocating Tachycardia-induced Dilated Cardiomyopathy: A Case Report - Fatih Battal; Şule Yıldırım; Hakan Aylanç; Fatih Köksal Binnetoğlu; Nazan Kaymaz; Celal Akdeniz (Haseki Tıp Bülteni, 2017)
We present a four-year-old girl who was admitted to our hospital with the complaints of dyspnea, tachypnea, cough, excess sweating and fatigue. Electrocardiogram (ECG) in the tachycardic girl showed inverted P waves in leads 2, 3 and aVF along with a P-R interval of 0.16 sec and an R-P interval of 0.28 sec. Transthoracic echocardiography revealed an enlarged and spherical left ventricle with diminished systolic functions. Holter ECG confirmed long R-P tachycardia with a rate of 140-160 beats/minute. She was diagnosed as having permanent junctional reciprocating tachycardia-induced dilated cardiomyopathy and successfully treated with catheter ablation and flecainide.